Geometric Design of Highways for Accommodation of More Traffic Volume with Increased Design Speed - Srikiran, S; Deepak Kumar, S; Venkatasubramanian, C; Muthu, D; Suriyanarayanan, S (International Journal of Engineering and Technology, 2018)
Road transport plays an important role in India’s economy. It enables the country’s transportation sector to contribute 6.1% towards India’s GDP. The road network in our country is considered as a critical factor to the country’s development, social integration and security needs of the country. The Government of India has promoted foreign investments in highway projects to bring out high standards and quality. India’s road network carries over 65% of freight and 85% passenger traffic. The traffic volume carried by the national highways almost exceeds the designed traffic volume, and hence the desired speed cannot be achieved. Thus, widening of highways becomes necessary. The population growth is also to be considered and hence provision for future widening is to be provided. Our paper deal with the geometric design for widening of NH-9 is carried out using MX-Bentley software as per IRC specifications. This design includes horizontal and vertical profiling throughout the stretch of the road, according to the existing topographic data. The radius of the curve has been increased to make a smooth curve. Also, the vertical profile has been designed based on the allowable gradient and sight distances. From this, accommodation of more traffic volume and increment of design speed seems to be possible.